1999
DOI: 10.1097/00006454-199904000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and control of vancomycin-resistant enterococci in a regional neonatal intensive care unit

Abstract: VRE can spread rapidly among newborns in a regional neonatal intensive care unit. Strict infection control measures can reduce the rate of VRE colonization among neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 20 publications
5
30
0
2
Order By: Relevance
“…Duration of hospital stay, use of vancomycin, third-generation cephalosporins, and central venous catheters were reported as the risk factors in NICU [7]. In our study duration of total antimicrobial therapy in VRE colonized patients were significantly longer as compared to negative cases.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Duration of hospital stay, use of vancomycin, third-generation cephalosporins, and central venous catheters were reported as the risk factors in NICU [7]. In our study duration of total antimicrobial therapy in VRE colonized patients were significantly longer as compared to negative cases.…”
Section: Discussionsupporting
confidence: 40%
“…Vancomycin-resistant enteroccocci has become an important nasocomial pathogen and thread for the last decade [7]. From its initial discovery in 1986, VRE has been reported worldwide [1,2,16] mostly responsible for colonizations, and less often as a nasocomial pathogen [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid spread of VRE among NICU patients was documented by Malik et al, who reported the spread of related strains of VRE to 40% of the NICU patient population (305). Two preterm infants developed bloodstream infection, and 33, including 11 of 13 babies who shared a room with the bacteremic babies, became colonized with VRE.…”
Section: Vol 17 2004 Infections In Very-low-birth-weight Infants 649mentioning
confidence: 96%
“…Assim é que mais de 80% das cepas de Staphylococcus epidermidis e pelo menos 60% das cepas de Staphylococcus aureus causadores de infecção nosocomial em unidades neonatais são resistentes à meticilina-oxacilina, ou seja, a antibióticos betalactâmicos, incluindo outras penicilinas, cefalosporinas, carbapenêmicos e combinação de drogas que contenham inibidores de beta-lactamases. A emergência de cepas de enterococcus resistentes à vancomicina tem sido documentada em unidades de terapia intensiva 42 , o que é temerário, pois estas bactérias são resistentes a todos os antibióticos disponíveis e têm o potencial de servirem como reservató-rios de genes de resistência a glicopeptídeos, que podem ser transferidos a outros patógenos ainda mais virulentos.…”
Section: Uso De Antimicrobianos E Infecção Hospitalar: a Necessidade unclassified